Contested environmentalism: the politics of waste in China and Russia. Issue 4 (7th June 2021) - Wu, Fengshi; Martus, Ellie
ABSTRACT: China and Russia provide critical insights into the nature of environmental politics under authoritarian governments. Developing a paired comparison of activism over waste management in both countries, we explore how environmental civil society interacts with the state and mobilizes social support. We find that despite greater political liberalization, NGOs in hybrid states such as Russia can still find it highly challenging to resist state pressure and introduce policy changes. In contrast, China, notwithstanding its harsher authoritarian system and the use of more repressive measures against social activism, can still be tested by a well-strategized NGO alliance. We challenge the linear logic of existing theories on environmental politics, which assume that social movements are all moving towards a defined end point (e.g. liberal democracy), and argue that environmental politics under authoritarian regimes is both dynamic and contested.